Investigation of neutron shielding properties depending on number of boron atoms for colemanite, ulexite and tincal ores by experiments and FLUKA Monte Carlo simulations - Korkut, Turgay; Karabulut, Abdulhalik; Budak, Gokhan; Aygun, Bunyamin; Gencel, Osman; Hancerliogullari, Aybaba (Elsevier BV, 2012)
(241)Am-Be source and three samples including different amounts of boron atoms per unit volume called colemanite, ulexite and tincal were used in total macroscopic cross section experiments. Also FLUKA Monte Carlo code was used to simulate total macroscopic cross sections, absorbed doses and deposited energies by low energy neutron interactions. Besides half value layers of samples were calculated and compared to paraffin. As a result, ascending concentration of boron atoms can enhance neutron shielding property of samples.
Keywords: Boron Compounds; Neutrons; Neutron Shielding; Radiation; Americium; Total macroscopic cross section; Fluka Monte Carlo Code; Boron ores; HVL; Hvl; Radiation Protection; Models, Chemical; Materials Testing; Boron Ores; Computer Simulation; Total Macroscopic Cross Section; Neutron shielding; FLUKA Monte Carlo code